ON THE SOCIO-POLITICAL HISTORY OF SAMARQAND BEK (Ustozlar uchun, 2024)
Samarkand province his own great the nature is productive lands and beautiful bog‘ - rog‘ lar with separate standing Bukhara important of the emirate political , economic and cultural from the centers one counted . Wait center dated Samarqand, XVIII century second half and XIX century the first in half in the emirate central h authority Mustah reduction and centralization in politics important role played